Análise da viabilidade econômica da execução de residência unifamiliar padrão popular em alvenaria estrutural de blocos de concreto em comparação ao sistema convencional brasileiro - Gavlik, Janaina (2019)
Owing to housing deficit that Brazil’s facing against a conventional building system with high costs and execution times, this present study is based on this problematic, aiming its comparation with another building system of structural masonry of hollow concrete blocks. The main goal of this research is to analyze the economic viability to execute a popular standard single-family residence of structural masonry with concrete blocks, and compare it to the conventional building system of masonry in ceramic bricks and concrete structure. For this purpose, two budgets were elaborated, one for each mentioned building system, of a popular standard single-family residence. Moreover, was performed an analysis of the viability of the investiment. The results indicate that the most economically viable is the structural masonry than traditional proccess and, through the conclusions, expects this system obtain more evidence in the national market, once this research testifies this system is economically advantageous when compared to the brazilian conventional system.